Karakteristik Cedera Ankle Sprain pada Pemain Futsal Mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar: Kajian Deskriptif dan Literatur Ilmiah - Abdillah Adipatria Budi Azhar; Sabrina Intan Zoraya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Ankle sprains are one of the most common musculoskeletal injuries among futsal players and have implications for both performance and sustained participation in sport. This study aimed to describe the characteristics of ankle sprain among student futsal players from the Faculty of Medicine, Universitas Islam Al-Azhar. The study was conducted among 26 respondents who were members of a futsal community using a quantitative descriptive method. Univariate analysis showed 58% of respondents reported a history of ankle sprain. Prominent intrinsic factors included body mass index, with 35% of respondents classified as having a normal BMI. Regarding extrinsic factors, 100% respondents played on vinyl-surfaced courts and 96% used standard futsal shoes. A total of 100% of respondents reported performing warm-up exercises before playing, while only 81% regularly performed ankle strengthening exercises. The use of taping or ankle braces was relatively low, reported by only 8% of respondents. This study concludes that ankle sprain among student futsal players remains a significant issue that requires comprehensive preventive strategies through the integration of neuromuscular training, muscle strengthening, routine warm-up exercises, and the use of taping or ankle braces.